Unshackling Press Freedom: A Catalyst for Environmental Protection in Indonesia - Fikri, Syukri Alamul (Indonesia Media Law Review, 2024)
Press freedom plays a pivotal role in environmental protection, especially in countries like Indonesia where environmental issues are pressing. This paper explores the relationship between press freedom and environmental protection in Indonesia, emphasizing how a free press can act as a catalyst for addressing environmental challenges. It discusses the current state of press freedom in Indonesia, the environmental issues the country faces, and the potential benefits of enhancing press freedom in promoting environmental conservation. Drawing upon case studies and empirical evidence, this paper argues that empowering the press can lead to greater accountability, transparency, and public awareness, thereby fostering stronger environmental governance and citizen participation. It also examines the challenges and opportunities in unshackling press freedom in Indonesia and proposes strategies for policymakers, media practitioners, and civil society to collaborate effectively in this endeavor.